THE KOREAN WAVE PHENOMENON AND ITS RELEVANCE TO THE COMPETITIVENESS OF LOCAL MSMES IN THE DIGITAL ERA - Rafi'Syaiim, Salsabila; Hilal, Syamsul; Budimansyah, Budimansyah (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The Korean Wave, or Hallyu, has emerged as a powerful global cultural phenomenon that significantly shapes consumer behavior and digital market dynamics across various countries, including Indonesia. The expansion of Korean popular culture encompassing K-Pop, K-Drama, K-Beauty, fashion, and culinary trends has generated substantial economic spillover effects that increasingly influence purchasing decisions, lifestyle preferences, and brand perceptions among Indonesian consumers. This literature review aims to analyze the relevance of the Korean Wave to the competitiveness of local Micro, Small, and Medium Enterprises (MSMEs) in the digital era by synthesizing findings from international and Indonesian scholarly sources. The study identifies that Hallyu has created both opportunities and challenges for local MSMEs. On the one hand, the trend stimulates innovation through the adoption of Korean-inspired product designs, digital marketing strategies, and cross-cultural branding approaches that enhance market visibility and engagement. On the other hand, the dominance of Korean cultural products intensifies competitive pressure, especially for MSMEs that lack digital literacy, creativity, or the ability to adapt to fast-changing consumer trends. The review highlights that MSMEs integrating Korean cultural elements such as aesthetic storytelling, influencer collaboration, and trend-based product modification tend to demonstrate stronger competitive advantage within digital marketplaces. Furthermore, strategic support from government institutions, digital platforms, and entrepreneurial training programs is essential to help MSMEs optimize opportunities stemming from global cultural trends. Overall, the Korean Wave presents a transformative cultural-economic landscape that compels Indonesian MSMEs to innovate, adapt, and strengthen their digital capabilities to remain relevant and competitive. This study contributes to understanding how cross-cultural influences shape MSME development and provides recommendations for enhancing resilience and competitiveness in the digital economy.